11. PERANAN LAOS, MYANMAR, DAN THAILAND DALAM MENANGANI PENYALAHGUNAAN PRODUKSI DAN PERDAGANGAN OPIUM DI KAWASAN SEGITIGA EMAS - Yanuarizki, Candra; Utomo, Tri Cahyo; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Association of South East Asian Nations (ASEAN) has a role to address drug trafficking inits area, thus formed a special agency to deal with this problem through a forum namedASEAN Senior Official on Drugs Matters (ASOD). ASOD, in cooperation with China,India, Laos, Myanmar, and Thailand announced Declaration of Chiang Rai, which focuseson opium production and trafficking in the Golden Triangle area. The declaration itselfreflects a common interest to control drug trafficking between Laos, Myanmar, andThailand. Based on this common interest, this research is developed to know theimplementation of Chiang Rai Declaration as a form their cooperation. Using liberalinstitutional theory, this research finds that cooperation between Laos, Myanmar, andThailand based on Declaration of Chiang Rai is implemented to address trafficking.Declaration Chiang Rai programs make Laos, Myanmar, and Thailand can collaborate toaddress opium trafficking more seriously. This research also finds that this cooperation isbased on the fact that those three countries have the same purpose, that is to maintain thestability in South East Asia.